In vivo detection of extrapancreatic insulin gene expression in diabetic mice by bioluminescence imaging. - Xiaojuan Chen; Courtney S Larson; Jason West; Xiaomin Zhang; Dixon B Kaufman (PLoS ONE)
Background Extrapancreatic tissues such as liver may serve as potential sources of tissue for generating insulin-producing cells. The dynamics of insulin gene promoter activity in extrapancreatic tissues may be monitored in vivo by bioluminescence-imaging (BLI) of transgenic mice Tg(RIP-luc) expressing the firefly luciferase (luc) under a rat-insulin gene promoter (RIP). Methods The Tg(RIP-luc) mice were made diabetic by a single injection of the pancreatic beta-cell toxin streptozotocin. Control mice were treated with saline. Mice were subject to serum glucose measurement and bioluminescence imaging daily. On day eight of the treatment, mice were sacrificed and tissues harvested for quantitative luciferase activity measurement, luciferase protein cellular localization, and insulin gene expression analysis. Results Streptozotocin-induced diabetic Tg(RIP-luc) mice demonstrated a dramatic decline in the BLI signal intensity in the pancreas and a concomitant progressive increase in the signal intensity in the liver. An average of 5.7 fold increase in the liver signal intensity was detected in the mice that were exposed to hyperglycemia for 8 days. Ex vivo quantitative assays demonstrated a 34-fold induction of the enzyme activity in the liver of streptozotocin-treated mice compared to that of the buffer-treated controls. Luciferase-positive cells with oval-cell-like morphology were detected by immunohistochemistry in the liver samples of diabetic mice, but not in that of non-treated control transgenic mice. Gene expression analyses of liver RNA confirmed an elevated expression of insulin genes in the liver tissue exposed to hyperglycemia. Conclusions BLI is a sensitive method for monitoring insulin gene expression in extrapancreatic tissues in vivo. The BLI system may be used for in vivo screening of biological events or pharmacologic activators that have the potential of stimulating the generation of extrapancreatic insulin-producing cells.